Control of Chaos in a Current Mode Controlled Buck Boost Converter Using Weak Periodic Perturbation Method - P. Sriramalakshmi; A. Kavitha; P. Sanjeevikumar; Tole Sutikno; Pandav Kiran Maroti; Vigna K. Ramachandaramurthy (Institute of Advanced Engineering and Science, 2017)
This paper analyses the nonlinear phenomena in current mode controlled buck-boost converter. The system undergoes various operating regions whenever there is a change in non linear elements presented in the system as well as in the loads. In this work, inductor current is considered as the reference for analysis.The results show that the converter enters into period-1, periodic doubling and chaotic regions as per the parameter (IL) variations. The proposed control strategy, weak periodic perturbation (WPP) method tries to stabilize the system from the chaotic behavior.The buck boost converter along with the control system is simulated using MATLAB/SIMULINK software tool and the results are presented.The hardware implementation of the system is done and the results are verified with the simulation results. It shows that the WPP can transform the system behaviour from the chaotic region to the periodic one.